The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/02626667.2013.853122
|View full text |Cite
|
Sign up to set email alerts
|

Bringing groundwater models to LIFE: a new way to assess water resource management options

Abstract: . Bringing groundwater models to LIFE: a new way to assess water resource management options. Hydrological Sciences Journal, 59 (3-4), 578-593.Abstract If management of water resources is to fully take into account the requirements of the environment, it will benefit from quantitative predictions of the ecological effects of river flow alterations. A significant relationship between flow reductions caused by groundwater abstraction and ecological conditions (as measured by relevant biotic indices) has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Hendriks et al (2014) reported that drainage and groundwater abstraction in sandy catchments in the Netherlands meant that low flows were reduced below the environmental flow criterion, whilst Kennen et al (2014) found that groundwater abstraction led to a 20% reduction in intolerant macro-invertebrates in New Jersey, USA, due to reduced river flow. Streetly et al (2014), working in the midlands of England, also found that flow reductions caused by The changing role of ecohydrological science in guiding environmental flowsgroundwater abstraction altered ecological conditions (as measured by relevant biotic indices).…”
Section: Historical Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Hendriks et al (2014) reported that drainage and groundwater abstraction in sandy catchments in the Netherlands meant that low flows were reduced below the environmental flow criterion, whilst Kennen et al (2014) found that groundwater abstraction led to a 20% reduction in intolerant macro-invertebrates in New Jersey, USA, due to reduced river flow. Streetly et al (2014), working in the midlands of England, also found that flow reductions caused by The changing role of ecohydrological science in guiding environmental flowsgroundwater abstraction altered ecological conditions (as measured by relevant biotic indices).…”
Section: Historical Contextmentioning
confidence: 99%
“…The science of environmental flows has also benefited from closer links with other aspects of hydrological science. For example, groundwater modelling assists with understanding groundwater-fed ecosystems (Kennen et al 2014, Streetly et al 2014 including those in permeable sandy substrata (Hendriks et al 2014).…”
Section: State Of the Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Ecological impacts occurred when the effect of abstraction exceeded 60% of Q75 flows regardless of water quality, habitat or seasonal effects. Streetly et al () combine this ecology–streamflow–groundwater pumping relationship with a calibrated regional groundwater model within an ELOHA framework to assess river reaches that are likely to be ecologically impacted by pumping and might consequently be at risk of failing to meet European Union Water Framework Directive standards.…”
Section: Existing Policies Regulations and Management Plansmentioning
confidence: 99%
“…Although the adoption of simple “rules of thumb” by water managers to make decisions about environmental flows is a pragmatic approach in the short‐term, it represents a risk to the integrity and biodiversity of the world's riverine ecosystems (Arthington et al , ). The need for environment flow assessment methods that quantify links between ecology and water resource pressures to provide accurate local scale assessments is also pressing given the potentially large financial investments required to deliver precautionary environmental flows (Streetly et al, ).…”
Section: Introductionmentioning
confidence: 99%